Diversely polarised sparse array design with minimum interelement spacing constraint for polarised pattern synthesis. Issue 5 (1st March 2020) - Shi, Shuli; Xu, Yougen; Zhao, Kang; Huang, Yunlin; Liu, Zhiwen
Abstract : The problem of optimised design of diversely polarised sparse array for joint synthesis of spatial and polarisation beampattern is addressed in this Letter. Two kinds of polarised array configurations, cocentred and non‐cocentred crossed‐dipole arrays, are considered. Minimum interelement spacing constraint along with non‐cocentred constraint are involved in the design methods by using two discrete linear operators. The optimisation process can be formulated as a mixed‐integer quadratically constrained programming problem which guarantees the optimal solution of the sparse array configuration. Comparison examples with state‐of‐the‐art method validate the advantages of the proposed method in terms of the reduction of required element number and the enlargement of adjacent element spacing.